Designing, Modelling and Analysis of The Edge Geometry of Linear Lathe Tool Bit - Sándor Bodzás; Sándor Pálinkás; Csaba Nemes (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2018)
In this publication, with the help of our modelling software we have designed and modelled the edge geometry of the linear lathe tool in the model space. Our aim has been to develop a program which calculates the appropriate edge geometry with the help of some input length and angle dimensions. This is modelled in a wire frame model in a kind a file format that can be easily opened in the latest CAD softwares – so if some later modifications are needed, that can be done easily on the model. With the help of Finite Element Simulation based on given loads, boundary conditions, technological parameters and material quality, an optimal edge geometry can be determined on the cutting tool for reaching the best cutting ratio.